2018
DOI: 10.1093/mnras/sty514
|View full text |Cite
|
Sign up to set email alerts
|

Baryonic distributions in galaxy dark matter haloes – II. Final results

Abstract: Re-creating the observed diversity in the organization of baryonic mass within dark matter haloes represents a key challenge for galaxy formation models. To address the growth of galaxy discs in dark matter haloes, we have constrained the distribution of baryonic and non-baryonic matter in a statistically representative sample of 44 nearby galaxies defined from the Extended Disk Galaxy Exploration Science (EDGES) Survey. The gravitational potentials of each galaxy are traced using rotation curves derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 82 publications
(129 reference statements)
2
13
0
Order By: Relevance
“…These values are consistent with Lelli et al (2016) who found M/L minimum and maximum values of ∼ 0.2 and ∼0.7 M /L respectively. The median value of the fixed M/L (0.5 M /L ) is similar to the fixed M/L assumed by Lelli et al (2016) and Richards et al (2018), who used 3.6 µm photometric data. The M/L value obtained using the MDM model is ∼4 times higher than the value of the BFM.…”
Section: Mass Models − Hα + Starssupporting
confidence: 74%
“…These values are consistent with Lelli et al (2016) who found M/L minimum and maximum values of ∼ 0.2 and ∼0.7 M /L respectively. The median value of the fixed M/L (0.5 M /L ) is similar to the fixed M/L assumed by Lelli et al (2016) and Richards et al (2018), who used 3.6 µm photometric data. The M/L value obtained using the MDM model is ∼4 times higher than the value of the BFM.…”
Section: Mass Models − Hα + Starssupporting
confidence: 74%
“…The decomposition of disk galaxies into bulge, disk and halo components is complex, and can lead to radically different results depending on assumptions, particularly regarding the mass-to-light ratios (e.g., Sofue 2016;Richards et al 2018). It is however unlikely that a three-dimensional baryonic component dominates most disk galaxies at scales larger than ∼ kpc.…”
Section: Discussionmentioning
confidence: 99%
“…Further Patsis et al (2009) used the findings of Boonyasait et al (2005) and studied the stellar and gas dynamics for this galaxy. Richards et al (2018b) in their study of the baryonic distributions in galaxy dark matter halo, observed NGC4068 through VLA-C configuration with velocity resolution 0.825 kms −1 . Wilcots et al (1996) and Thuan et al (2004) observed NGC4861 using VLA-D and VLA-C configuration with channel resolution 5.2 kms −1 and 2.6 kms −1 respectively and sensitivity ∼ 1 mJy/beam for both cases.…”
Section: Sample Selectionmentioning
confidence: 99%
“…Furthermore, the HI cubes with its 3D kinematic modeling done with the recently developed tools to fit the tilted ring model (Rogstad et al 1974) by Józsa et al (2007) and Di Teodoro & Fraternali (2015) gives us the detailed kinematics and dynamics of the galaxies. The rotation curve, when combined with optical or infrared observation, provides the mass model of the galaxies, i.e., the radial distribution of different components (star, gas and the dark matter) of galaxies and the scope to test different dark matter halo profiles (see Richards et al 2018a;Kurapati et al 2018bKurapati et al , 2020. The interferometric cubes are also helpful to find the 3D distribution of the atomic gas and its volumetric properties.…”
Section: Introductionmentioning
confidence: 99%